Blastomycosis in Quebec (1981–90): Report of 23 Cases and Review of Published Cases from Quebec - G St-Germain; G Murray; R Duperval (Canadian Journal of Infectious Diseases)
Twenty-three cases of blastomycosis were reported in a survey conducted in the province of Quebec from 1981–90. Thirteen patients resided south of the St Lawrence River and the other 10, north. Two small geographical clusters were apparent in and around the cities of Sherbrooke and Quebec. The male to female ratio was 1.6:1 and the median age was 47 years (range 26 to 77). Lung involvement was observed in 19 cases and was the only site involved in 11. Cutaneous manifestations were reported in 11 cases while bone infection (three cases) and central nervous system (CNS) infections were also noted. Diagnosis was confirmed by culture in 21 cases and by histopathology in two cases. Of the 21 culture-positive cases, 12 strains of Blastomyces dermatitidis were isolated from lungs, nine from skin, and one each from bone and brain. Serodiagnostic tests by immunodiffusion or complement fixation were positive for only one of the 10 patients known to have been tested. Ten patients were treated with amphotericin B, 11 with ketoconazole, one with fluconazole and eight underwent surgery. While amphotericin B was used in eight of the 10 earliest treated cases, ketoconazole was administered in 10 of the 13 more recent cases. Of the patients for whom follow-up data have been obtained, 21 are reported cured (one of whom was not treated) and one patient died of another cause. This survey confirms that blastomycosis is a rare disease in this endemic area and that patterns of therapy are changing.